Evidence for the presence of growth-promoting factors in Lombok Turbinaria murayana extract stimulating growth and yield of tomato plants (Lycopersicum esculentum Mill.). (20th July 2020) - Sunarpi, Haji; Kurnianingsih, Rina; Ghazali, Mursal; Fanani, Rizka Azzahral; Sunarwidhi, Anggit L.; Widyastuti, Sri; Nikmatullah, Aluh; Prasedya, Eka S.
Abstract: Many studies have evidenced the negative effects of synthetic fertilizers toward the environment and also the crop products itself. Hence, the improvement of organic fertilizers is necessary to resolve this problem. Seaweeds or marine macroalgae are considered to be an excellent natural resource in different aspects of agricultural fields. Brown macroalgae Turbinaria murayana (TM) is often found in Indonesian coastal areas with high bioavailability throughout the year. This study evaluated the potentials of TM as biofertilizer in tomato plants ( Lycopersicum esculentum Mill.). Evaluation of phytohormones present in TM crude extract was conducted with high performance liquid chromatography (HPLC). Macro and micronutrients available in TM crude extract were determined by atomic absorbance spectroscopy (AAS). A concentration of 4% TM crude extract was applied to tomato plants. The vegetative properties of the treated tomatoes were observed such as growth and yield. Current results evidenced the presence of growth-promoting factors (kinetin, gibberellin and ABA) and essential elements (N, P, K, Ca, Fe and Mn) in TM crude extract. Application of 4% TM extract to tomato plants significantly increased vegetative growth compared to untreated plants; plant height, leaf number and branch number, approximately 58.4%, 87.5% and 200%, respectively. Similar results were also found in the response of generative growth. Application of 4% liquid extract significantly improved flower and fruit number compared to control; 53.6% and 125%, respectively. These results suggest that TM crude extract is a potential source for developing organic fertilizers.